On the methodological concept of foreign language education - Kulgildinova, T.; Zhumabekova, G. (KSU Publ., 2018)
The foreign paradigm of education is considered from the standpoint of the cognitive-linguocultural approach in the article. It is specified that modern achievements of foreign language education are connected with the substantiation of the conceptualization of the world by man, the understanding of the language and its role in cognitive processes. It is found out that phenomena of categorization of the cognitive-linguistic and cultural methodology of foreign language education, which allow to use scientific results in a complex scientific object - thinking-language-communication. The theoretical and practical essence of modern cognitivelinguoculturological methodology of foreign language education is substantiated, which serves as a conceptual platform for the training of teaching staff. This is one of the modern theories of training specialists, which is based on the cognitive-conceptual complex study of language-culture-personality. Approach to the problems of education from the standpoint of modern linguistic science is indicated, taking into account the relationship of language and man to reality through the functioning of language karting of the world of ethnic groups, that allows students to form intercultural communication. In this regard, the article examines the theoretical origins of foreign language education, analyzes the main works of teachers, psychologists and linguists who formed this scientific branch. It is specified that in the training of specialists of a foreign language specialty it is important to teach students to use the inventory of language tools (in the form of statements and discourses) in order to implement the didactic tasks for carrying out the intercultural communication in various situations.
Шетел тілін оқытудың əдіснамалық тұжырымдамасы туралы
О методологической концепции иноязычного образования
Keywords: cognitive-linguocultural methodology; foreign-language education; intercultural competence; cognitive skills